The MOM1 complex recruits the RdDM machinery via MORC6 to establish de novo DNA methylation - Zheng Li; Ming Wang; Zhenhui Zhong; Javier Gallego-Bartolomé; Suhua Feng; Yasaman Jami-Alahmadi; Xinyi Wang; James Wohlschlegel; Sylvain Bischof; Jeff A. Long; Steven E. Jacobsen (Nature Communications, 2023)
Abstract MORPHEUS’ MOLECULE1 (MOM1) is an Arabidopsis factor previously shown to mediate transcriptional silencing independent of major DNA methylation changes. Here we find that MOM1 localizes with sites of RNA-directed DNA methylation (RdDM). Tethering MOM1 with an artificial zinc finger to an unmethylated FWA promoter leads to establishment of DNA methylation and FWA silencing. This process is blocked by mutations in components of the Pol V arm of the RdDM machinery, as well as by mutation of MICRORCHIDIA 6 (MORC6). We find that at some endogenous RdDM sites, MOM1 is required to maintain DNA methylation and a closed chromatin state. In addition, efficient silencing of newly introduced FWA transgenes is impaired in the mom1 mutant. In addition to RdDM sites, we identify a group of MOM1 peaks at active chromatin near genes that colocalized with MORC6. These findings demonstrate a multifaceted role of MOM1 in genome regulation.